2020
DOI: 10.1097/meg.0000000000001959
|View full text |Cite
|
Sign up to set email alerts
|

Decreased number of colonic tuft cells in quiescent ulcerative colitis patients

Abstract: Background Colonic tuft cells are epithelial chemosensory cells involved in barrier integrity, modulation of inflammatory responses and gut homeostasis. Recent evidence indicates an involvement of tuft cells in ulcerative colitis pathogenesis, though mechanisms remain largely unknown. Here, we quantified the colonic tuft cell population in patients with quiescent ulcerative colitis as compared to patients without identified colonic disease (controls). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 38 publications
1
25
0
5
Order By: Relevance
“…Two studies (42,43) describe a population of human colonic DCLK1 + TCs, however, Leppänen et al (44) reported that human colonic epithelial DCLK + cells have a morphology similar to absorptive enterocytes rather than a classical TC shape, thus questioning whether DCLK1 marks human TCs. In this context we recently tested a commercially available antibody (ab31704) on human colonic material, and failed to obtain convincing immunolabeling for DCLK1 (23), a conclusion also reached by Banerjee et al (40). Differences in DCLK1 immunoreactivity in human GI epithelium could be due to differences in protocol and fixation methods or that human TCs simply do not express DCLK1.…”
Section: Identification Of Human Intestinal Tcsmentioning
confidence: 88%
See 1 more Smart Citation
“…Two studies (42,43) describe a population of human colonic DCLK1 + TCs, however, Leppänen et al (44) reported that human colonic epithelial DCLK + cells have a morphology similar to absorptive enterocytes rather than a classical TC shape, thus questioning whether DCLK1 marks human TCs. In this context we recently tested a commercially available antibody (ab31704) on human colonic material, and failed to obtain convincing immunolabeling for DCLK1 (23), a conclusion also reached by Banerjee et al (40). Differences in DCLK1 immunoreactivity in human GI epithelium could be due to differences in protocol and fixation methods or that human TCs simply do not express DCLK1.…”
Section: Identification Of Human Intestinal Tcsmentioning
confidence: 88%
“…Differences in DCLK1 immunoreactivity in human GI epithelium could be due to differences in protocol and fixation methods or that human TCs simply do not express DCLK1. By contrast, cyclooxygenase enzyme (COX)-1 has been identified as a reliable marker for human TCs (9,21,23). Gerbe et al (9) were first to validate COX-1 as a marker for human TCs by co-staining for other markers such as SRY-box transcription factor 9 (SOX9) and hematopoietic prostaglandin D synthase.…”
Section: Identification Of Human Intestinal Tcsmentioning
confidence: 99%
“…Several clinical studies have independently reported that reduced tuft cell numbers in the intestinal tract are associated with ileal Crohn's disease (Banerjee et al, 2020) and quiescent ulcerative colitis (Kjaergaard et al, 2021), suggesting that insufficient tuft cells are closely related to the pathology of inflammatory bowel diseases. Since we newly propose a IPMK-tuft cell-IBD axis in this study, targeting IPMK has the potential to be a novel therapeutic strategy to treat IBD.…”
Section: Discussionmentioning
confidence: 99%
“…While not extensive, a small number of studies have examined ETCs in irritable bowel syndrome (IBS), inflammatory bowel disease (IBD), and upon enteric viral infection, prompting us to ask questions about the implications of these findings in the context of enteric parasitic infections [13,[116][117][118][119][120][121].…”
Section: Tuft Cells and Other Gastrointestinal Disordersmentioning
confidence: 99%
“…Thus, infection with Hymenolepis diminuta (rat cestode), Schistosoma mansoni (blood fluke/trematode parasite), and parasitic nematodes (H. polygyrus, Necator americanus (human hookworm), T. spiralis, and Trichuris suis) has been found to alleviate the severity of disease in murine models of colitis (which shares some features with human IBD) [128][129][130][131]. ETC frequency and IL-25 level were both found to be downregulated in human colonic biopsies and mouse models of colitis [13,[117][118][119], suggesting that one benefit of helminth therapy would be the correction of this deficit. Succinate supplementation in the diet of TNF ∆ARE/+ mice, which spontaneously developed a Crohn's disease-like ileitis, resulted in less injury and reduced inflammation [13].…”
Section: Parasites As Immunotherapy For Inflammatory Bowel Disease: the Role Of Tuft Cellsmentioning
confidence: 99%